Obesity and Overweight Problems Among Individuals 1 to 25 Years Following Acute Rehabilitation for Traumatic Brain Injury: A NIDILRR Traumatic Brain Injury Model Systems Study. Issue 4 (July 2018) - Dreer, Laura E.; Ketchum, Jessica M.; Novack, Thomas A.; Bogner, Jennifer; Felix, Elizabeth R.; Corrigan, John D.; Johnson-Greene, Doug; Hammond, Flora M.
Abstract : Objective: Examine the prevalence of weight classifications and factors related to obesity/overweight among persons 1 to 25 years following traumatic brain injury (TBI) using the Traumatic Brain Injury Model Systems national database. Design: Multicenter, cross-sectional, observational design. Setting: Traumatic Brain Injury Model Systems inpatient rehabilitation facilities. Participants: Persons ( N = 7287) 1, 2, 5, 10, 15, 20, or 25 years after TBI who required inpatient acute rehabilitation. Main Outcome Measures: Body mass index, demographic characteristics, functional, health, satisfaction with life, and global outcomes. Results: Overall postinjury weight prevalence rates were 23% obese, 36% overweight, 39% normal, and 3% underweight. Higher rates for obesity and overweight problems were associated with increasing time since injury. Younger (18-19 years) and older (80+ years) age, those in a vegetative state, and those reporting excellent health were less likely to be obese. Individuals with a history of hypertension, heart failure, or diabetes were more likely to be obese. Conclusions: Being obese or overweight presents a health risk in the years following rehabilitation for TBI. The findings support the need for longitudinal studies and highlight the advisability of monitoring weight and promoting healthy lifestyle behaviors over time in survivors of TBI.